Predictive study on Mechanical strength of Lightweight concrete using MRA and ANN - et. al., R. Pranamika, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The lightweight concrete is preferred over regular density concrete as it which reduces the dead load of the structure due to its lower density. The reduction in dead load of the structure, resulting in a considerable decrease in the size of structural elements and reinforcements; thereby, the building's cost can be reduced. The lightweight concrete is achieved through natural lightweight aggregates, artificial lightweight aggregates, coconut shells, oil palm shells, aeration in concrete, etc. The mechanical properties like compressive strength, tensile strength, density depend upon lightweight aggregate, fine aggregate, super-plasticizer, cement content, water-cement ratio, etc. The mechanical properties can also be predicted using artificial intelligence from the existing data. This research aims to predict lightweight concrete's mechanical properties using MRA and ANN accurately.